The counter-effects of market regulation - Franz Peter Lang (Intereconomics, 1990)
Regulation can have counter-effects that work against the interests of those who advocate it, in both centrally-planned and market economies. Little research on these effects has been carried out so far, with the result that they have been ignored by policymakers.
Keywords: 330